(-3ln+6lnx)=6

Simple and best practice solution for (-3ln+6lnx)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-3ln+6lnx)=6 equation:


Simplifying
(-3ln + 6lnx) = 6

Remove parenthesis around (-3ln + 6lnx)
-3ln + 6lnx = 6

Solving
-3ln + 6lnx = 6

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Reorder the terms:
-6 + -3ln + 6lnx = 6 + -6

Combine like terms: 6 + -6 = 0
-6 + -3ln + 6lnx = 0

Factor out the Greatest Common Factor (GCF), '3'.
3(-2 + -1ln + 2lnx) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(-2 + -1ln + 2lnx)' equal to zero and attempt to solve: Simplifying -2 + -1ln + 2lnx = 0 Solving -2 + -1ln + 2lnx = 0 Move all terms containing l to the left, all other terms to the right. Add '2' to each side of the equation. -2 + -1ln + 2 + 2lnx = 0 + 2 Reorder the terms: -2 + 2 + -1ln + 2lnx = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1ln + 2lnx = 0 + 2 -1ln + 2lnx = 0 + 2 Combine like terms: 0 + 2 = 2 -1ln + 2lnx = 2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 36*x^4=4.5 | | -5y+x=-3 | | x^2+0.106x-0.106=0 | | 9(x+2)=7x+25 | | 24=60-8x | | s-(-10)=2 | | 24=60-x | | 3x+12=6x+5 | | 4=16-n | | 4(2x+4)-13= | | 5x^3+21x^2-21x+5=0 | | 5(n+8)=10 | | 5x^2-5x-30=30 | | 50t+125=30t+200 | | 5x-x+4x=7-3 | | x+2.75=6 | | 7x-4=6.5 | | 9-6x=4-3x+3x | | 4-2x=14x+15 | | 2t+6=t+8 | | 0.5sin(2x)=cos(x) | | 3(x-2)=2x+16 | | 14=12-10y | | 4(w-9)=6w-38 | | -5n-8(1+n)=-8 | | -16-4y=46 | | 2x^2+20x=22 | | 49x-64x^2=0 | | x^2+0.5x=0.25 | | -8x+13=-3(x-6) | | x^2-0.5x-0.25=0 | | x^2+0.5x-0.25=0 |

Equations solver categories